High Dosages of Equine Chorionic Gonadotropin Exert Adverse Effects on the Developmental Competence of IVF-Derived Mouse Embryos and Cause Oxidative Stress-Induced Aneuploidy - Lin, En; Li, Zhiling; Huang, Yue; Ru, Gaizhen; He, Pei (Frontiers in Cell and Developmental Biology, 2021)
Gonadotropins play vital roles in the regulation of female reproductive ability and fertility. Our study aimed to determine the effects of superovulation induced by increasing doses of equine chorionic gonadotropin [eCG; also referred to as pregnant mare serum gonadotropin (PMSG)] on the developmental competence of mouse embryos and on aneuploidy formation during in vitro fertilization (IVF). eCG dose-dependently enhanced the oocyte yield from each mouse. Administration of 15 IU eCG significantly reduced the fertilization rate and the formation of four-cell embryos and blastocysts and increased the risk of chromosome aneuploidy. The IVF-derived blastocysts in the 15 IU eCG treatment group had the fewest total cells, inner cell mass (ICM) cells and trophectoderm (TE) cells. Moreover, more blastocysts and fewer apoptotic cells were observed in the 0, 5, and 10 IU eCG treatment groups than in the 15 IU eCG treatment group. We also investigated reactive oxygen species (ROS) levels and variations in several variables: mitochondrial membrane potential (MMP); active mitochondria; mitochondrial superoxide production; adenosine triphosphate (ATP) content; spindle structures; chromosome karyotypes; microfilament distribution; and the expression of Aurora B [an important component of the chromosomal passenger complex (CPC)], the spindle assembly checkpoint (SAC) protein mitotic arrest deficient 2 like 1 (MAD2L1), and the DNA damage response (DDR) protein γH2AX. Injection of 15 IU eCG increased ROS levels, rapidly reduced MMP, increased active mitochondria numbers and mitochondrial superoxide production, reduced ATP content, increased abnormal spindle formation rates, and induced abnormalities in chromosome number and microfilament distribution, suggesting that a high dose of eCG might alter developmental competence and exert negative effects on IVF-obtained mouse embryos. Additionally, the appearance of γH2AX and the significantly increased expression of Aurora B and MAD2L1 suggested that administration of relatively high doses of eCG caused Aurora B-mediated SAC activation triggered by ROS-induced DNA damage in early mouse IVF-derived embryos for self-correction of aneuploidy formation. These findings improve our understanding of the application of gonadotropins and provide a theoretical basis for gonadotropin treatment.